BUSINESS VALUATION AND ESG FACTORS – AN INTEGRATED APPROACH - Andreea IURAȘ; Dorina-Nicoleta POPA; Natalia Ioana FOLTEAN (Annals of the University of Oradea: Economic Science)
Considering the rising popularity of reporting ESG (environment, social, governance) related actions, a natural curiosity was born among investors, and other parties, whether it can affect the business value or not. The answers regarding the integration of ESG factors into business valuation are still contradictory, with the tendency towards those who positively support this statement. This study aims to observe some of the potential correlations between ESG factors reported and business valuation. To understand the connectivity, we reviewed key works from the literature regarding this topic and looked for the optimal approach for integrating ESG factors into the business valuation. In this regard, an empirical study case on Romanian companies was developed. The investigated period was from 2020 to 2022. The purpose of the study was to identify the correlations between the most used profitability indicators, price multiples, EV/EBITDA, and ESG Scores. Results showed that the company with the highest ESG score had better profitability, and was the best performing on the market. However, because ESG reporting is still a new challenge for Romanian companies, and measuring the ESG score is still in its infancy stage, we proposed that domestic companies should prepare better to report and disclose sustainability data and regulators should support the companies by developing and promoting sustainability and ESG reporting and disclosure principles, ethics and guides